Musical Activity During Life Is Associated With Multi-Domain Cognitive and Brain Benefits in Older Adults - Böttcher, Adriana; Zarucha, Alexis; Köbe, Theresa; Gaubert, Malo; Höppner, Angela; Altenstein, Slawek; Bartels, Claudia; Buerger, Katharina; Dechent, Peter; Dobisch, Laura; Ewers, Michael; Fliessbach, Klaus; et al. (Frontiers in Psychology, 2022)
Regular musical activity as a complex multimodal lifestyle activity is proposed to be protective against age-related cognitive decline and Alzheimer’s disease. This cross-sectional study investigated the association and interplay between musical instrument playing during life, multi-domain cognitive abilities and brain morphology in older adults from the DELCODE study. Participants reporting long-term musical activity during life (n=70) were compared to controls without musical activity (n=70) well-matched for reserve proxies of education, intelligence, socioeconomic status and physical activity. Participants with musical activity outperformed controls in global cognition, working memory, executive functions, language, and visuospatial abilities, with no effects seen for memory. The musically active group had greater gray matter volume in the somatosensory area, but did not differ from controls in higher-order frontal, temporal, or hippocampal volumes. However, the association between gray matter volume in distributed frontal-to-temporal regions and cognitive abilities was enhanced in participants with musical activity compared to controls. We show that long-term musical activity during life relates to better late-life cognitive abilities and greater brain capacities in older adults. Musical activity may serve as a multimodal enrichment strategy that could help preserve cognitive and brain health in late life. Longitudinal and interventional studies are needed to support this notion.